The Possibilities of Bim Quality Control in the Game Development Environment - Volařík, Tomáš; Kuruc, Michal; Kratochvíl, Richard; Vystavěl, Ondřej (ISPRS, 2022)
The quality control of the BIM model to be delivered is one of the most important steps in the process of information modelling. Quality control can take place on several levels. First of all, it is a control of geometric parameters, especially a control of the relative accuracy of the resulting model with respect to the modelled real object. Another type of quality control can be a check of the completeness of the model, whether the resulting model contains all the elements that are to be included in the model according to the requirements. MEP equipment such as fire extinguishers, for example, is a substantial content of BIM models. This may also be related to the required level of LOD, e.g. whether these elements are modelled with the required level of detail. Furthermore, the visual properties of the individual elements can be checked, for example whether the surface finish of the wall corresponds to reality. Subsequently, database and descriptive information of individual elements should be checked, such as technical parameters of various items of technical equipment of MEP content. This article describes variants of the publication of a building information model for the purposes of BIM model quality control. The procedure of creating the final application in the game development environment Unreal Engine (Epic Games) is described on the example of a BIM model of a historical building from the middle of the 19th century.

The quality control of the BIM model to be delivered is one of the most important steps in the process of information modelling. Quality control can take place on several levels. First of all, it is a control of geometric parameters, especially a control of the relative accuracy of the resulting model with respect to the modelled real object. Another type of quality control can be a check of the completeness of the model, whether the resulting model contains all the elements that are to be included in the model according to the requirements. MEP equipment such as fire extinguishers, for example, is a substantial content of BIM models. This may also be related to the required level of LOD, e.g. whether these elements are modelled with the required level of detail. Furthermore, the visual properties of the individual elements can be checked, for example whether the surface finish of the wall corresponds to reality. Subsequently, database and descriptive information of individual elements should be checked, such as technical parameters of various items of technical equipment of MEP content. This article describes variants of the publication of a building information model for the purposes of BIM model quality control. The procedure of creating the final application in the game development environment Unreal Engine (Epic Games) is described on the example of a BIM model of a historical building from the middle of the 19th century.
The Possibilities of Bim Quality Control in the Game Development Environment
Keywords: heritage building information modelling (HBIM); laser scanning; quality control; as-built documentation; visualization; heritage building information modelling (HBIM); laser scanning; quality control; as-built documentation; visualization